2018
DOI: 10.1016/j.ymthe.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Virus Combination Therapy: Killing One Bird with Two Stones

Abstract: Over the last 60 years an eclectic collection of microbes has been tested in a variety of pre-clinical models as anti-cancer agents. At the forefront of this research are a number of virus-based platforms that have shown exciting activity in a variety of pre-clinical models and are collectively referred to as oncolytic viruses. Our true understanding of the potential and limitations of this therapeutic modality has been substantially advanced through clinical studies carried out over the last 25 years. Perhaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 131 publications
0
84
0
1
Order By: Relevance
“…Accordingly, IFN-1 concentration was detectable in the media of macrophages infected by the Maraba virus (Figure 2B). MG1 Maraba is an oncolytic virus (OV) that is being tested in phase1/2 clinical trials, and acts through multiple antitumor mechanisms including direct tumor cell lysis, modulation of tumor microenvironment to a more proinflammatory state and generation of tumor-specific T-cells (Martin and Bell 2018;Breitbach 2020). Our findings raise the speculation that when tumor-associated macrophages are infected by Maraba virus, A3A promotes their proinflammatory polarization, creating a favorable microenvironment for development of antitumor immunity, while at the same time enhancing antiviral response.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, IFN-1 concentration was detectable in the media of macrophages infected by the Maraba virus (Figure 2B). MG1 Maraba is an oncolytic virus (OV) that is being tested in phase1/2 clinical trials, and acts through multiple antitumor mechanisms including direct tumor cell lysis, modulation of tumor microenvironment to a more proinflammatory state and generation of tumor-specific T-cells (Martin and Bell 2018;Breitbach 2020). Our findings raise the speculation that when tumor-associated macrophages are infected by Maraba virus, A3A promotes their proinflammatory polarization, creating a favorable microenvironment for development of antitumor immunity, while at the same time enhancing antiviral response.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to combine oncolytic viruses with different immune characteristics to overcome antiviral immune responses and exert synergistic effects. Similarly, it has been demonstrated that bacteria can synergize with oncolytic viruses (31). For example, Le Boeuf et al demonstrated that VSV (Vesicular Stomatitis Virus) combined with VACV (Vacienia Virus) improved antitumor response in immunodeficient and immunocompetent mouse tumor models (32).…”
Section: Combination Therapies With Oncolytic Virusesmentioning
confidence: 99%
“…One of the potential pitfalls of using OV to deliver CAR T cell target antigens to tumor cells is the suboptimal or non-uniform infection of solid tumors 12,13 . To address this, we assessed whether CAR T cell-mediated killing of virally-infected tumor cells could enhance the release of oncolytic viral particles for subsequent infection of surrounding tumor cells.…”
Section: Cd19-car T Cell-mediated Tumor Killing Promotes the Early Rementioning
confidence: 99%